eDNA monitoring detects new outbreak wave of corallivorous seastar (Acanthaster cf. solaris) at Lizard Island, Great Barrier Reef - Sven Uthicke; Jason R. Doyle; Maria Gomez Cabrera; Frances Patel; Madi J. McLatchie; Peter C. Doll; Josie F. Chandler; Morgan S. Pratchett (Coral Reefs, 2024)
Crown-of-thorns seastar (CoTS, Acanthaster cf. solaris ) outbreaks remain a significant cause of coral loss on the Great Barrier Reef (GBR) and across the West-Pacific Ocean. Previous outbreaks on the GBR have only been discovered once fully established, which constrains opportunities for effective control. Early detection of outbreaks would provide an important opportunity for early intervention and increase understanding of outbreak cause(s). Here, we assess the utility of environmental DNA (eDNA) monitoring to detect the initiation of a population outbreak at Lizard Island over five years (2019–2023), compared with density estimates obtained using Scooter-Assisted Large Area Diver-based (SALAD) surveys. At each of the five eDNA sampling sites, 30 replicate samples were collected annually and analysed with CoTS-specific primer sets and digital droplet PCR. Both methods detected distinct increases in CoTS densities from 2020/21 onwards, indicating the start of a new population outbreak. A large part of the observed variation in eDNA (expressed as the percentage of positive samples) was explained by changes in recorded CoTS density, confirming that eDNA data provide a quantitative estimate for adult CoTS abundance. SALAD surveys and eDNA are new and complementary monitoring methods that facilitate early detection of CoTS outbreaks, which will enable more effective management intervention.